A Science Agenda to Inform Natural Resource Management Decisions in an Era of Ecological Transformation. (17th November 2021) - Crausbay, Shelley D; Sofaer, Helen R; Cravens, Amanda E; Chaffin, Brian C; Clifford, Katherine R; Gross, John E; Knapp, Corrine N; Lawrence, David J; Magness, Dawn R; Miller-Rushing, Abraham J; Schuurman, Gregor W; Stevens-Rumann, Camille S
Abstract: Earth is experiencing widespread ecological transformation in terrestrial, freshwater, and marine ecosystems that is attributable to directional environmental changes, especially intensifying climate change. To better steward ecosystems facing unprecedented and lasting change, a new management paradigm is forming, supported by a decision-oriented framework that presents three distinct management choices: resist, accept, or direct the ecological trajectory. To make these choices strategically, managers seek to understand the nature of the transformation that could occur if change is accepted while identifying opportunities to intervene to resist or direct change. In this article, we seek to inspire a research agenda for transformation science that is focused on ecological and social science and based on five central questions that align with the resist–accept–direct (RAD) framework. Development of transformation science is needed to apply the RAD framework and support natural resource management and conservation on our rapidly changing planet.